Income Disparities and Regional Economic Potential in East Kalimantan Province as the National Capital (IKN) New Capital City of Indonesia Nusantara - Yolanda Gorrety Espinosa S; I Wayan Suparta; Resha Moniyana (Lafadz Jaya Publisher, 2024)
The government has announced plans to move the national capital (IKN) to East Kalimantan Province and this was agreed at the DPR RI Plenary Meeting in early 2022. The aim of this research is to analyze disparities in income & economic potential between Regency/City regions in the IKN region of East Kalimantan Province. The data used in this research uses secondary data from 2017-2022. The analytical tools used are the Williamson Index, Location Quotient and Shift Share Analysis and Klassen Typology. The software used for analysis is Microsoft Excel 2010. The research results show that the Williamson Index figure in East Kalimantan Province for the last five years is 0.473, indicating that the value is in the medium level inequality category. Meanwhile, the classification of regions based on region uses the Klassen Typology with a regional approach divided into: Developed and fast growing regions, West Kutai Regency and East Kutai Regency; Developed but depressed areas, namely Bontang City and Kutai Kartanegara Regency; Areas that are developing quickly but are not advanced, namely, Balikpapan City, Samarinda City, Berau Regency and Mahakam Ulu Regency; The relatively underdeveloped areas are Paser Regency and North Penajam Paser Regency. Research results based on LQ analysis state that there are 2 cities that have the largest total base sectors, namely Balikpapan and Samarinda. If you look at the shift share analysis with indicators for assessing regional share growth components in East Kalimantan Province, there are 7 sectors that have positive values, and there are only 3 sectors that still have negative values.